Analisis Pasar Pembangunan Apartemen Mahasiswa Institut Teknologi Sumatera - Nurzukhrufa, Antusias (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The more rapid development of the Sumatra Institute of Technology will have an impact on the demand for student housing needs. The residential rental business in the form of rented houses and boarding houses is increasing. However, there are no rental housing for students with the concept of apartments around the Sumatra Institute of Technology built by developers. Even though the target market is clear, namely students, it is necessary to do a detailed market analysis. This study aims to analyze the market for student apartment development around the Sumatra Institute of Technology. The research method used is qualitative with descriptive analysis techniques. Data on aspects of market analysis were explored through website searches, literature studies, interviews, questionnaires, site surveys and documentation. This study found that from the market analysis aspects that have been analyzed, the Sumatra Institute of Technology student apartments have the potential to be built.